The use of blockchain for collecting value-added tax on online cross-border trade in digital goods - Kabwe, Ruddy Kapasula (University of Pretoria, 2024)
The collection of value-added tax from the cross-border supply of digital goods remains a challenge for tax authorities around the world. South Africa is no different. The traditional methods of collecting VAT from the supply of digital goods relies on the honesty of the consumer and on the supplier to account for and remit VAT to the tax authorities in the jurisdiction where the goods are consumed. The traditional collection models are often unreliable, inefficient, burdensome, and expensive for the consumers and the suppliers. The adoption of blockchain technology as a model to collect VAT on the cross-border supply of digital goods has the potential to alleviate the compliance burden on consumers and suppliers of digital goods, improve the efficiency of tax administration, and reduce VAT fraud. Importantly, blockchain technology can create trust between tax authorities, suppliers of digital goods, and consumers. This thesis critically discusses the advantages and disadvantages of implementing blockchain technology for the collection of VAT on the cross-border supply of digital goods in South Africa. This thesis unpacks the consideration factors for policymakers in the implementation of blockchain technology for the collection of VAT on cross-border trade in digital goods. The thesis makes recommendations for the South African VAT Act to be amended to make provision for the collection of VAT by utilising blockchain technology.
URI: https://repository.up.ac.za/handle/2263/97005
Keywords: Anonymisation; Blockchain technology; Decentralisation; Digital goods; Private blockchain; Smart contracts; Taxpayer privacy; Value-added tax

La ley de comercio electrónico en el sistema contractual ecuatoriano - Palma, Vanessa Alexandra Henríquez; Toapanta, Angela Dayana Miranda; Navarrete, Cristobal Teodoro Veliz; Vega, Johana Alexia Fierro (Polo del Conocimiento, 2024)
El comercio electrónico es una nueva forma de comercio en auge, constituida por transacciones comerciales que se llevan a cabo por medio de Internet. En este sentido, el contrato electrónico es un acuerdo de voluntad que se establece mediante el uso de herramientas electrónicas en donde las partes se comprometen a cumplir lo que se establezca, conservando las características básicas del contrato tradicional y su contenido surte efecto legal. Ahora bien, el conjunto de leyes regulatorias es fundamental para garantizar la transparencia y la seguridad en las transacciones electrónicas, lo cual genera confianza entre las partes involucradas en las actividades de comercio electrónico. En consecuencia, y dada la importancia de la legislación en esta materia, el propósito de la presente investigación es plasmar las generalidades del sistema contractual del comercio electrónico en el Ecuador, específicamente su marco legal. El enfoque metodológico de la investigación es una revisión bibliográfico – documental. Las bases legales internacionales para el desarrollo de la normativa contractual en materia de comercio electrónico en Ecuador, tiene base en la Comisión de las Naciones Unidas para el Derecho Mercantil Internacional (CNUDMI) y el conjunto de textos legislativos emanados de este ente. Especialmente la Ley Modelo, la cual tiene el propósito de colaborar con los Estados en la reforma y modernización de sus leyes acerca del procedimiento arbitral. Igualmente, estas normas especiales se complementan con normas comunes a los contratos con fundamentos tradicionales en la incursión de esta nueva forma de expresar la voluntad de las partes, tales como la Constitución de la República del Ecuador, el Código Civil, el Código de Comercio, el Código Orgánico General de Procesos (COGEP), la Ley Orgánica de Defensa del Consumidor y, más recientemente, la Ley Orgánica para la Transformación Digital y Audiovisual.
Keywords: Comercio; Comércio Eletrônico; Contractual; Direito; Electronic commerce; Electrónico; Ley; Sistema

Loi type de la CNUDCI sur l'utilisation et la reconnaissance internationale de la gestion de l'identité et des services de confiance - United Nations Commission on International Trade Law (United Nations, 2024)

Les intérêts économiques du cyberconsommateur à l’épreuve de l’offre électronique - Majilo Pombou, Linda Judith (Revue Africaine des Réflexions Juridiques et Politiques, 2024)
Le commerce électronique peut s’effectuer par le biais d’un acte juridique appelé contrat. Le contrat peut être entendu comme un acte qui constate une convention entre deux ou plusieurs personnes. À l’origine de tout contrat électronique, il existe une offre électronique. Cette offre électronique renferme un certain nombre de spécificités. La problématique de cette étude vise à savoir si les mécanismes juridiques encadrant l’offre électronique sont propices à la sécurisation du consommateur qui contracte par voie électronique Cette étude sur la protection du consommateur à l’épreuve de l’offre électronique a eu pour objectif de montrer l’effort législatif effectué en vue de protéger le consommateur qui recourt au contrat électronique. La méthodologie a porté sur la collecte et l’analyse documentaire, pour saisir les dimensions de cette protection. Les résultats indiquent, que, les textes adoptés tendent à sécuriser les transactions en ligne et surtout à assurer au consommateur un niveau de protection considérable.
Keywords: Consommateur; Consumer; Electronic offer; Intérêt; Offre électronique; Protection